Pelatihan Kader Kesehatan dalam Melakukan Deteksi Dini Katarak di Desa Jatimulya Dukuh Gemahsari Kec. Suradadi, Kab. Tegal - Ani Ratnaningsih; Uswatun Insani; Natsya Kartika Cahya; Berlian Nur Aini; Nava Oktavia Rini (Lembaga Pengembangan Kinerja Dosen, 2024)
.Quality of life impairment, eye complications, and total vision loss are complications if cataracts are not detected or detected too late. Early vision problems detection can prevent these complications. “Posbindu” is the first line of health services in the community in Indonesian country, that place could be used to early detection of visual impairment. The community health worker could do early detection cataract if they have this knowledge and skills. The training community health worker have been done with Cataract Early Detection Module. This module contains: knowledge about cataracts, cataracts early detecetion using the